2018
DOI: 10.5888/pcd15.180079
|View full text |Cite
|
Sign up to set email alerts
|

National Food Affordability: A County-Level Analysis

Abstract: The purpose of this study was to explore the sociodemographic factors that contribute to food affordability across space, with specific emphasis on rural and urban differences in the United States. A regression analysis was used to predict food affordability from several predictors in rural and urban areas, with a subanalysis of Appalachian and Delta counties. Rural households had significantly higher food expenditures to income ratios compared with urban counties; Appalachian and Delta counties had the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…The findings from our focus groups add to the growing body of research illuminating the health inequities Appalachian communities face. It is important to note the rapid decline of the socioeconomic landscape in rural communities compared with their urban counterparts ( 27 ). Although common barriers, such as affordability and access to healthy food, exist among low-income residents of both rural and urban communities, Appalachia has unique challenges, including low population density, geographic isolation, and persistent poverty, that amplify these barriers ( 7 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from our focus groups add to the growing body of research illuminating the health inequities Appalachian communities face. It is important to note the rapid decline of the socioeconomic landscape in rural communities compared with their urban counterparts ( 27 ). Although common barriers, such as affordability and access to healthy food, exist among low-income residents of both rural and urban communities, Appalachia has unique challenges, including low population density, geographic isolation, and persistent poverty, that amplify these barriers ( 7 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a qualitative study of 15 low-income Appalachian residents found that only 1 person regularly visited a farmers market, citing pricing and inconvenience as barriers (24). Although respondents reported generally positive attitudes toward farmers markets, the economic and cultural environmental landscapes and other barriers do not make them a plausible intervention for all Appalachian communities (25,26).…”
Section: December 2020mentioning
confidence: 99%
See 1 more Smart Citation
“…There may be also be a false perception that rural areas have access to local agricultural products in abundance [ 11 ], although in many contexts these products are outsourced or largely not intended for human consumption [ 15 ]. Rural residents with low-income also use more of their total budget for food purchases than urban counterparts [ 16 ]. Additionally, according to some research, access to jobs and other opportunities that mitigate food insecurity is often based on one’s social and family network, particularly in the rural South [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Built food environments are comprised of constructed places that provide food, including grocery stores, convenience stores, farmers markets, food assistance programs, restaurants, schools, and other retail outlets [18]. In the built food environment, Native American and rural communities face unique challenges to cultivating healthy diets, including limited infrastructure [19], long distances to food outlets [20,21], lower quality [22][23][24] and less affordable foods [25] and overall fewer healthy options in their food environment [26]. Commodities, or the Food Distribution Program on Indian Reservations (FDPIR), was created to improve food access for reservation communities, but has been unsuccessful in providing a balanced diet or one that supports Native American food systems [27].…”
Section: Introductionmentioning
confidence: 99%